Using planar near-field measurement for microwave holographic diagnosis - Theunissen, W. H.(Wilhelmus Hendrikus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Electronics)) -- University of Stellenbosch, 1990.